2017
DOI: 10.1080/21642850.2016.1276459
|View full text |Cite
|
Sign up to set email alerts
|

Parenting, the other oldest profession in the world – a cross-sectional study of parenting and child outcomes in South Africa and Malawi

Abstract: Background Parenting quality is important in child development. In the presence of HIV poverty and life stress, parenting may be challenged and child development affected. Methods This study examines cross-sectional associations of situational factors such as poverty, mental health, HIV status, living with a biological parent, and stigma with good parenting and child outcomes (n=989; age=4–13 years) within the Child Community Care study (South Africa and Malawi). A parenting measure was created from 10 varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…The focus group discussions explored the level of knowledge of children’s need for social and emotional care, and the need to maintain open communication between children and caregivers. They also investigated parenting knowledge and skills in managing behavioural problems, the kinds of discipline employed in households, and monitoring and supervision of children, as these factors are associated with improved child well‐being outcomes in poor urban areas in other studies (Gorman‐Smith, Tolan, & Henry, ; Sherr et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The focus group discussions explored the level of knowledge of children’s need for social and emotional care, and the need to maintain open communication between children and caregivers. They also investigated parenting knowledge and skills in managing behavioural problems, the kinds of discipline employed in households, and monitoring and supervision of children, as these factors are associated with improved child well‐being outcomes in poor urban areas in other studies (Gorman‐Smith, Tolan, & Henry, ; Sherr et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…A cross sectional study from South Africa and Malawi, sampled nine hundred and eighty nine children aged between four to thirteen years and examined child reports from caregivers. Questionnaires were constructed and data was analysed using Statistical Package for Social Science (SPSS 20), univariate and multivariate regression analysis by Sherr et al (2017).Consequently, the findings showed that being a biological parent was associated with higher parenting scores. Good parenting is associated with increased child self-esteem.…”
Section: Parenting Styles Used By Guardians On Youthful Offendersmentioning
confidence: 99%
“…demonstrates an association between poverty and child outcomes. Poverty has been negatively associated with good parenting in a study conducted in Malawi and South Africa, arguing that caregivers are overly occupied with providing the basic needs of the children that they lack the time and energy to maintain a positive relationship with their child (Sherr et al, 2017). The Integrated Parenting Framework…”
Section: Povertymentioning
confidence: 99%